Stability analysis of a multistep method for excavating high spoiled slopes on the Guigu expressway: a case study - Jingtao Zhang; Qiaoshan Xing; Xu Du; HuanHuan He; Han Xia (Scientific Reports)
Abstract This study examines the stability of a spoiled heap along the Guigu Expressway. Through onsite investigations, laboratory tests, numerical analyses, and onsite monitoring, this case study evaluates the reinforcement effect of a multistep method for disposing of spoiled heaps. The results show that applying the multistep method to treat spoiled heaps significantly improves their stability, as demonstrated by numerical simulation. The results of the circular sliding surface method (f s = 1.56) and the fold line sliding surface method (f s = 1.58) both satisfy the stability requirements of the current standard (f s > 1.3). The cost of using the multistep method to treat medium-sized spoiled heaps is 1.11 million CNY, effectively improving the economic efficiency of construction. According to the results of onsite monitoring, no significant deformation occurred in the spoiled slope, with both the final settlement and maximum displacement measuring less than 10 mm.